Competitive Behavior of Isotactic Polybutene-1 Polymorphs in Electrospun Membranes and Solution Cast Films via Cold Crystallization. Issue 7 (3rd August 2022) - Kashif, Muhammad; Li, Huihui; Liu, Junteng; Rasul, Sadia; Ullah, Qudrat; Liu, Yong
Abstract: Isotactic polybutene-1 (iPB-1) generally crystallizes into metastable form II upon non-isothermal crystallization from the melt. The inevitable and prolonged transition of this form to form I is a drawback of numerous iPB-1 applications. In this study, electrospun (e-spun) membranes and solution cast films were prepared from the same solution, but they exhibited different crystalline behaviors. The fresh e-spun and solution cast samples contained hexagonal form I/I′ and tetragonal II, but the former was dominant in the e-spun samples. This finding was attributed to the stress-induced crystallization during electrospinning. The e-spun blend membrane of iPB-1/isotactic polypropylene (iPP) (75/25) was investigated via time-based heating-cooling protocols to obtain a stable form I′ exclusively. Upon annealing the findings revealed a distinct amount of form I′ for the e-spun blend at a quenching value of −25 °C, wherein metastable form II was suppressed entirely. The results indicate that form I′ generation in both types of samples is characterized by a confined nucleation mechanism, but in e-spun iPB-1/iPP membranes, the malleable structure favors the thermodynamics characteristics of form I′ upon heating which also reinforces the transition kinetics. The amount of form I′ was found to be directly proportional to the heating time at 185 °C, whereas it was inversely proportional to the quenching and crystallization temperatures.